الضّوابط الشّرعيّة للتّجميل غير الجراحي - باسو, حسام الدين; باسو -, إشراق; باسو -, فاطمة الزهرة (University of Eloued-جامعة الوادي, 2018)
ىوذه الموذكرة بعنوان:"ال و ووابة ال و ورزية لللهوحميوأ وير الجراحوي"، لدرسونا يهوا الإنوكاليوة الآتية:ىأ اللهوحميأ ير الجراحي اّئ زلع إطلاقوو يم قيوود ب ووابة لحودلد لللإ اّبوة زلوع ىذا اللهوساؤل سرنا ل ق ت وة اسولههللناىا بالمخحوث الأولل الموراد باللهحميوأ، لالمخحوث الثواب بينووا يو حك اللهوحميأ لينوازو، يو ا المخحث الثالث ذكرنا يو يى و ال و وابة ال و رزية لللهوحميأ ير الجراحوي، لبعو الأ ثلوة اللهو خيقيووة لوو )الونوم ، الوصوأ، الونو ( ، لتلصو دراسولهنا إلى تقييود اللهوحميأ ير الجراحي ب وابة نرزيوة. Abstract This thesis is entitled "Shariahical rules for non surgical beautification". where we studied the following problem: is all the non-surgical beauty permissible? or is it limited by limits and rules. In order to answer this question, we respected the following steps. in the first section, we present the language and terminology definition and synonymous of the beautification. In the second section, we present the ruling on beautification and its types. in the third section, we mentioned the most important Shariahical rules for non surgical beautification, and some of the applied models for it (Namss, wasl, Tattoo). finally, in the last section, we summaraze our study, by restriction of the non-surgic beautification by Shariahical rules and limits.
مذكرة ليسانس
Keywords: الضوابط الشرعية/التجميل الغير جراحي; Contrôles de la charia/chirurgie esthétique non chirurgicale